Morphological Analysis of Dare OUrt River Channel by the Rozgen Model(Case Study: Emarat Dam to the Confluence of Aras River) - Arsalan Mehrvarz; Agil Madadi; Fariba Esfandyari; Masoud Rahimi (تحقیقات کاربردی علوم جغرافیایی)
River morphology holds significant importance in the fields of geomorphology and river management and engineering. The marginal sections of rivers have consistently undergone changes in their riverbeds due to various social and economic factors. The Dare Ourt River, located in the Ardabil province, represents a permanent river that has experienced frequent floods and alterations in its channel morphology in recent periods. In this study, the Dare Ourt river was thoroughly analyzed using the Rosegen model at levels one and two. To conduct this study effectively, detaied data such as 1:2000 river topographic maps, hydrometric data, and boundary conditions from the Ardabil Regional Water Authority were collected and utilized. Furthermore, the HEC-RAS hydrodynamic model was employed to extract the primary indices of the Rosegen model with greater accuracy. The outcomes revealed that the majority of the river sections exhibit a C6c type, characterized by an alluvial substrate. Additionally, other dominant types observed within the four examined ranges include B6c, E6b, F6, and D. Field visits also confirmed a transition in the river type from C to F within range 4, which presents challenges for the reconstruction and restoration of the river in type F. As a recommendation, it is advised to implement restrictions to prevent the river from transitioning into type F.